Extraction, Characterization and Storage Stability of Oils from Selected Plant Seeds - Nyam, Kar Lin (2009)
There is a great demand for renewable sources of raw materials that have nutritional and industrial potential. To meet the increasing demand for vegetable oils, improvements are being made with conventional crops as well as with selected plant species that have the ability to produce unique, desirable fats and oils. The physicochemical properties and chemical composition of oil extracted from five varieties of plant seeds (bitter melon, Kalahari-melon, kenaf, pumpkin and roselle) were examined by established methods. Most of the quality indices and fatty acid compositions showed significant (P < 0.05) variations among the extracted oils. The oils were rich in tocopherols, with γ-tocopherol as the major component in all oil samples. Among the phytosterols, β-sitosterol was the major phytosterol extracted from the five plant-seed oils.Enzymatic extraction of oil from Kalahari-melon seeds was investigated and evaluated by response surface methodology. Two commercial protease enzyme products were separately used: Neutrase® 0.8 L and Flavourzyme® 1000 L from Novozymes (Bagsvaerd, Denmark). Response surface methodology (RSM) was used to model and optimize the reaction conditions, namely concentration of enzyme (2-5 g/100 g of seed mass), initial pH of mixture (pH 5- 9), incubation temperature (40-60 °C), and incubation times (12-36 h). The optimal conditions for Neutrase 0.8 L were enzyme concentration of 2.5 g/100 g, initial pH of 7, temperature at 58°C and incubation time of 31 h, yielding an oil recovery of 68.58 ± 3.39%. The optimal conditions for Flavourzyme 1000 L were: enzyme concentration of 2.1 g/100 g, initial pH of 6, temperature at 50 °C and incubation time of 36 h, yielding a 71.55 ± 1.28% oil recovery. The physicochemical properties of oil from Kalahari-melon seed were determined following extraction with petroleum ether and aqueous-enzymatic methods. The free fatty acid, peroxide, iodine and saponification values of the oils extracted using these two methods were found to be significantly (P < 0.05) different. No significant (P > 0.05) difference was observed between the melting points of the oils obtained from solvent and aqueous-enzymatic extractions. Enzyme-extracted oil tended to be light-colored and more yellow in color, compared with solvent-extracted oil. Fatty acids and phenolic acids in enzymeextracted oils were comparable to the solvent-extracted oil. The oils extracted with these two methods differed in the composition of their phytosterol and tocopherol contents, but no significant (P > 0.05) difference between the two enzyme-extracted oils was observed Supercritical carbon dioxide extraction of oil from Kalahari-melon and roselle-seeds were investigated in this study. Response surface methodology (RSM) was used to model and optimize the extraction conditions, namely pressure (200-400 bar), temperature (40-80 ºC) and supercritical fluid flow rate (10-20 mL/min). The optimal processing conditions for Kalahari-melon-seed oil recovery and phytosterol concentration were pressure of 300 bar, temperature of 40 °C and supercritical fluid flow rate of 12 mL/min. These optimal conditions yielded a 76.3% oil recovery and 836.5 mg/100 g of phytosterol concentration. The results indicate that the roselle-seed oil recovery was optimal, with a recovery of 102.61% and a phytosterol composition of 727 mg/100 g at the relatively low temperature of 40 °C, a high pressure of 400 bar and at a high supercritical fluid flow rate of 20 mL/min. Tocopherol-enriched oil from Kalahari-melon and roselle-seeds was extracted by supercritical fluid extraction with carbon dioxide (SFE-CO2). The optimal SFE-CO2 conditions for the extraction of tocopherol-enriched oil from Kalahari-melon seeds were extraction pressure of 290 bar, extraction temperature of 58 ºC and flow rate of carbon dioxide of 20 mL/min. The optimum conditions for roselle-seeds were extraction pressure of 200 bar, extracting temperature of 80 ºC and flow rate of carbon dioxide of 20 mL/min. These optimum conditions yielded a tocopherol concentration of 274.74 and 89.75 mg/100 g oil from Kalahari-seed and roselle-seed, respectively. During 6 months of storage of Kalahari-melon-seed and roselle-seed oils at both 4 ºC and room temperature in the darkness, changes occurred in the content of fatty acids, phytosterols and tocopherols, and in the presence of primary and secondary oxidative products. These seed oils were obtained from the seeds of Kalahari melon (Citrullus lanatus) and roselle (Hibiscus sabdariffa Linn.) by supercritical carbon dioxide (SC-CO2). As expected, statistically significant differences were observed in the content of fatty acids, phytosterols and tocopherols, and in the presence of primary and secondary oxidative products in Kalahari-melon-seed and roselle-seed oils throughout the storage. The quality indices peroxide and anisidine values increased during the 6 months storage time. After storage, degradation parameters may change because of lipid oxidation.